Microarray Analysis of Visceral Adipose Tissue in Obese Women Reveals Common Crossroads Among Inflammation, Metabolism, Addictive Behaviors, and Cancer - Rolando Martínez-Romero; Susana Aideé González-Chávez; Victor Roberto Urías-Rubí; Víctor Manuel Gómez-Moreno; Manlio Favio Blanco-Cantero; Héctor Mario Bernal-Velázquez; Arturo Luévano-González; César Pacheco-Tena (Journal of Obesity)
Conclusion: VAT confers a complex and blended pathogenic transcriptomic profile in obese patients, where abnormal processes are mainly controlled by activating intracellular signaling pathways that exhibit a high degree of redundancy. Identifying shared cross points between those pathways could allow specific targeting treatments to exert a widespread effect over multiple pathogenic processes.